(untitled) (Leiden, 2005)
This two volume book contains about 160 papers that were presented at the IV International Seminar on Structural Analysis of Historical Constructions that was held from 10 to 13 November, 2004 in Padova Italy. The book are devoted to the possibilities of numerical and experimental techniques in the maintenance of historical structures. In this respect, the papers, originating from over 30 countries, are subdivided in the following areas:· Historical aspects and general methodology,· Materials and laboratory testing,· Non-destructive testing and inspection techniques,· Dynamic behavior and structural monitoring,· Analytical and numerical approaches,· Consolidation and strengthening techniques,· Historical timber and metal structures,· Seismic analysis and vulnerability assessment,· Seismic strengthening and innovative systems,· Case studies.Structural Analysis of Historical Constructions is a valuable source of information for scientists and practitioners working on structure-related issues of historical constructions
Keywords: Structural analysis (engineering)